The Strategies in Learning English Language Used By Civil Engineering Students of Sintuwu Maroso University - Ingriyani Yohana Rawung; Sherliane Trisye Poai (Journal on Education, 2023)
The Strategy is used by the students in learning English to help them achieve the objective of language learning. Learning English language was involved in learning reading skill, writing skill, listening skill and speaking skill. Students has their own strategy in learning. Each students used their strategy depend on their pation. The used of strategy in language learning is needed to study. The objective of this research is to describe the English Language Learning Strategy used by Civil Engineering students in New Normal Era. The subject of the research was 82 students of Civil Engineering Students that follow the Basic English Subject in Sintuwu Maroso University Poso. Survey resarch is used in This research as the method. The data was colleceted by questionnaire. The result of the research obtained in Learning English Language Used By students Civil Engineering of Sintuwu Maroso University used many learning strategies in learning English. Those learning strategies were Cognitive, memory, social, and compensation strategies